Phenotypic and molecular characterization of neisseria gonorrhoeae isolated in Rio de Janeiro, Brazil, 2002–2003 - Barreto, Nero A.; Sant’anna, Raquel R.P.; Silva, Luisa B.G.; Uehara, Aline A.; Guimarães, Renata C.; Duarte, Isabele M.; Asensi, Marise D. (Brazilian Journal of Sexually Transmitted Diseases, 2004)
Introduction: along of antimicrobial era Neisseria gonorrhoeae have been developing resistance to several agents. It is estimated the occurrence of morethan 1,5 million new cases for year in Brazil and the emergence of the vigilance and dissemination of resistant strains must be periodically monitorated.Objective:evaluate the resistance, phenotypic and molecular characterization of gonococcus isolated in the metropolitan area of Rio de Janeiro betweenFebruary 2002 and June 2003, establishing basic information for further studies. Demographic profile of the patients with gonorrhea was determined.Method:samples of Neisseria gonorrhoeae isolated consecutively were tested for penicillin, tetracycline, azithromycin, ciprofloxacin, ceftriaxone and clo-ranfenicol using the E-test method to determine the Minimum Inhibitory Concentration (MIC). All the strains were tested for β-lactamase, plasmidialanalysis, serotyping and Pulsed-Field Gel Electrophoresis (PFGE) to study the genetic variability. The demographic characteristics of the patients wereobtained in medical file. Result:of the 115 tested samples, 10 (8.7%) were β-lactamase producing (PPNG), 88 (76.5%) had intermediary resistance topenicillin and 17 (14.8%) were sensitive. For tetracycline 39 (33.9%) were resistant, 37 (32.2%) had intermediary resistance and 39 (33,9%) were sensiti-ve. The resistance mediated by plasmid to tetracycline (TRNG, MIC ≥16 μg/mL) was detected in 20% of the isolate. To cloranfenicol, 4 (3.4%) wereresistant, 14 (12.2%) had intermediary resistance and 97 (84.5%) were sensitive. Were found 23 (20%) isolates with reduced susceptibility to azithromycin(MIC 0.25 – 0.5 μg/mL) and 2 (1.7%) with reduced susceptibility to ciprofloxacin (MIC = 0.5 μg/mL). All the samples were sensitive to ceftriaxone.Among PPNG, we found three distinct type of plasmids, the Asia (4.4 Mda), Africa (3.2 Mda) and Toronto (3.05 Mda) types. The predominant serogroupwas I-B/W II/III in about 90 % of the samples. Conclusion: the resistance surveillance to antimicrobial is important to monitorate the emergence andspread of resistant strains helping in therapeutic choice. In the area of Rio de Janeiro, penicillin and tetracycline are not recommended for the treatment ofgonorrhea and the use of azithromycin demands attention. The phenotypic and genotypic analyses of the studied samples will give comparative instrumentsfor future epidemiological studies. Our patients with gonorrhea are white men, young (average 22 years old), singles, heterosexuals, with multiple partners,with low level of education and familiar income, and continually exposed to risks of acquiring sexually transmitted diseases.